A Note on Accelerated Dollar Averaging - Wilson, George W. (Management Science, 1961)
The policy of accelerated dollar averaging as discussed by William T. Morris is an excellent contribution (Morris, W. T. 1959. Some analysis of purchasing policy. Management Sci. 5 (4, July).) is essentially correct. The analysis, however, merits extension beyond the rather abbreviated treatment given in the article cited. Dollar averaging is a type of procurement policy whereby a given amount of money is spent at each purchasing opportunity. The amount actually bought at each period is then a function of the price prevailing at that time.